Plato’s theory of the highest principles of being - Woszczyk, Agnieszka (Folia Philosophica, 2009)
Review of Bogdan Dembiński's book: Plato's Late Science. The Relationship Between Ontology and Mathematics. Katowice: University of Silesia Press, 2003.